Smith–Lemli–Opitz Syndrome: Oral Characteristics and Risk Factors for Caries Development - Dorota Olczak-Kowalczyk; Aneta Witt-Porczyk; Paula Piekoszewska-Ziętek; Małgorzata Krajewska-Walasek (Biomedicines)
Background/Objectives: Smith–Lemli–Opitz syndrome is a metabolic autosomal recessive disease, characterized by congenital defects, with concomitant psychomotor developmental delay. The symptoms are variable and depend on the clinical form of the disease. The aim of this study was to assess the prevalence and types of oral abnormalities in children and adolescents with Smith–Lemli–Opitz syndrome. Methods: The study enrolled 30 patients, including 15 subjects with Smith–Lemli–Opitz syndrome, confirmed by a genetic examination. We performed an extra- and intraoral examination, paying attention to the presence of dysmorphic features, including the shape and symmetry of the face; the condition of the skin and lips; the gingival and hygienic status; dental caries; lesions of non-carious origin; abnormalities of size, shape, and number; and alignment of teeth in the dental arch. Results: Patients in the study group presented with micrognathia, a short neck, ptosis, and an upturned nose. More frequently than in the control group, we observed occlusal abnormalities and dental crowding, anatomical abnormalities or gingivitis. The prevalence of dental caries in both groups was similar; however, the study group recorded higher dmft and DMFT values. Conclusions: The phenotypic features of patients with Smith–Lemli–Opitz syndrome increase their risk of developing dental caries and gingivitis.